2014
DOI: 10.1002/jmv.24086
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and characterization of BK and JC polyomaviruses in urine samples of renal transplant patients in Southern Brazil

Abstract: The human polyomaviruses JC (JCPyV) and BK (BKPyV) are widespread in the human population. Following the primary infection, virus reactivation may lead to nephropathy and graft rejection in renal transplant patients. This study was carried out to access the presence of BKPyV and JCPyV DNA in urine samples collected from renal transplant patients (n = 92) and healthy individuals (n = 88) in Porto Alegre, Rio Grande do Sul. The samples were submitted to a nested PCR. A significantly higher frequency (P < 0.001) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
11
1
2
Order By: Relevance
“…The same subtypes of JCPyV (1 and 3) and the subgroup of BKPyV (I) characterized in the water samples were found in a previous study with urine samples collected in the same geographic region (Comerlato et al, 2015), reinforcing that the polyomaviruses detected in urban waters belong to the same subtypes that have been excreted by the local population. This is the first report on the presence and genetic diversity of BKPyV and JCPyV circulating in this region of the South of Brazil.…”
Section: Jcpyv and Bkpyv Characterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…The same subtypes of JCPyV (1 and 3) and the subgroup of BKPyV (I) characterized in the water samples were found in a previous study with urine samples collected in the same geographic region (Comerlato et al, 2015), reinforcing that the polyomaviruses detected in urban waters belong to the same subtypes that have been excreted by the local population. This is the first report on the presence and genetic diversity of BKPyV and JCPyV circulating in this region of the South of Brazil.…”
Section: Jcpyv and Bkpyv Characterizationsupporting
confidence: 79%
“…Asymptomatic infections are common in humans. Serological and virological studies show that more than 80% of adults harbor antibodies to BKPyV or JCPyV (Shah et al, 1973;Bodaghi et al, 2009;Egli et al, 2009;Khanna et al, 2009), and both viruses have been found in the urine of up to 53.4% of asymptomatic, immunocompetent individuals (Chehadeh et al, 2013;Comerlato et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Особенно тяжелые проблемы ВК вирусы вызывают у пациентов на фоне лекарственного подавления иммунитета, когда происходит реактивация вирус ной инфекции с виремией и вирурией и развитием иногда фатальных осложнений. Особую актуаль ность представляет своевременная лабораторная диагностика ПВИ, направленная на оперативное выявление возбудителя и определение индивиду альной количественной оценки вирусной нагрузки с целью выработки адекватных подходов к лечению [12][13][14].…”
Section: Discussionunclassified
“…развитие криза отторжения, лимфопролифератив ных заболеваний у пациентов с трансплантирован ной почкой [8][9][10][11][12][13][14][15]. H. Shimohata и соавт.…”
Section: оценка вклада герпесвирусной инфекции в развитие и прогрессиunclassified
“…More recent publications on multiplex PCR for both viruses are based on the methodology described by Fedele et al 19 which can, as shown, generate non-specific results, and also the methodology proposed by Bofil-Mas et al . 20 .…”
mentioning
confidence: 99%